Подібні та відмінні ознаки освіти дорослих країн ЄС (Франції, Німеччини, Данії, Бельгії, Угорщини) та англомовних країн (США, Канади, Великої Британії) - Орос Ільдіко; Orosz Ildikó; Oros Ildiko (МНУ імені В. О. Сухомлинського, 2018)
Резюме. Вивчення і узагальнення досвіду розвинених країн світу дає можливість сформувати уявлення про характер загальних проблем, що мають місце у світовому освітньому просторі стосовно освіти дорослих, переконатись, що освіта дорослих нині є одним із пріоритетних напрямів політики багатьох країн. Нами виділено подібні ознаки освіти дорослих. Визначено тенденції розвитку системи неформальної освіти дорослих цих країн на основі спільних ознак. На основі проведеного аналізу нами виявлені і розбіжності в ознаках освіти дорослого населення зазначених англомовних та країнах Європейського Союзу. Найбільше концептуальних положень стосовно системи освіти дорослих розроблено у Великій Британії.

Abstract. Studying and generalizing the experience of developed countries of the world gives an opportunity to form an understanding of the nature of the common problems that exist in the world educational environment with regard to adult education, to ensure that adult education is now one of the priority directions of policy in many countries. We have highlighted similar signs of adult education. The education of adult EU countries (France, Germany, Denmark, Belgium, Hungary) and English-speaking countries (USA, Canada, UK) covers a set of structural elements that ensure their dynamic development: legislative framework, educational institutions and centers, educational programs, with the labor market, non-governmental organizations, and public associations. The adult education of the countries understudy represents a set of formal and informal learning, and adult education in the countries is part of the context of lifelong education. The contingents of adult students of the analyzed countries are : the unemployed, pensioners, the disabled, representatives of national minorities, migrants. Adult education management is predominantly under the control of the Ministry of Education in different countries, although there is now a tendency towards decentralization to varying degrees. The education of adults from different countries is funded mainly by the government and non-governmental organizations. The tendencies of development of system of informal education of adults of the countries on the basis of common features are determined. On the basis of the analysis we have revealed and differences in the signs of education of the adult population of these English-speaking countries and the European Union. In particular, in France, the main structure that provides vocational training and raising the skills of adults on a national scale is GREETA; universities are in second place. Universities and colleges, centers for adult education and retraining, vocational schools, numerous associations, and commissions are providers of adult education in other countries understudy. But in the United States, Great Britain, Canada, France, there are also public schools for retirement age (Third Age Universities). In Germany, significant services in the field of non-formal education are provided by churches, trade unions, which testify to the significant development of non-formal education. There are abolitionist types of this type: if the term "continuing education" in Germany is defined as the continuationorre instatement of organizational training for a certain period of adulthood, the ninth UK, and continued, and renewable education is a separate branch of adult education that has its own definition, tasks, develops based on relevant concepts. The most conceptual framework for adult education has been developed in the UK.
Similar and variable changes in adult education of Eu Countries (France, Germany, Denmark, Belgium, Hungary) and the english-speaking countries (USA, Canada, Great Britain)
http://nbuv.gov.ua/UJRN/Nvmdup_2018_3%282%29__42
Keywords: освіта дорослих; подібні та відмінні ознаки; країни ЄС; англомовні країни; формальне, неформальне та інформальне навчання; adult education; similar and distinctive features; EU countries; English-speaking countries; formal, non-formal and informal learning